PROFILING GLYCOL-SPLIT HEPARINS BY HPLC/MS ANALYSIS OF THEIR HEPARINASE-GENERATED OLIGOSACCHARIDES() - Alekseeva, Anna (2012)
Glycol-split (gs) heparins, obtained by periodate oxidation / borohydride reduction of heparin currently used as anticoagulant and antithrombotic drug, are arousing increasing interest in anti-cancer and anti-inflammation therapies. These new medical uses are favored by the loss of anticoagulant activity associated with glycol-splitting-induced inactivation of the antithrombin III (AT) binding site. The structure of gs-heparins has not been studied yet in detail. In this work, an ion-pair reversed-phase chromatography (IPRP-HPLC) coupled with electrospray ionization mass spectrometry (ESI-MS) widely used for unmodified heparin has been adapted to the analysis of oligosaccharides generated by digestion with heparinases of gs-heparins usually prepared from porcine mucosal heparin. The method has been also found very effective in analyzing glycol-split derivatives obtained from heparins of different animal and tissue origin. Besides the major 2-O-sulfated disaccharides, heparinase digests of gs-heparins mainly contain tetra- and hexasaccharides incorporating one or two gs residues, with distribution patterns typical for individual gs-heparins. A heptasulfated, mono-N-acetylated hexasaccharide with two gs residues has been shown to be a marker of the gs-modified AT binding site within heparin chains.